STRATEGI KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Mia Noprika; Ngadri Yusro; Sagiman Sagiman (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2020)
This study aimed to find out a portrayal of the principal's strategies in improving educational quality at SDN 81 in Lebong Regency, Bengkulu. This study used a qualitative approach with engaging the principal of SDN 81 of Lebong as the key informant. Data collection techniques deployed observation and interviews. Subsequently, the analysis of data adapted Miles’ et al approach subsuming data selection, data display, verification, and conclusion drawing. This study concluded that the principal’s strategies included ways to improve the qualities of teachers alongside students’ academic and non-academic achievements. The strategic implementation extended to involving teachers in training activities and seminars on education, conducting tutoring activities (bimbel), providing special remedial and extracurricular activities in the form of sports and arts development, organizing Try-Out, and providing additional learning hours for students who would take National Examination, School Exams, and others. In addition, in improving facilities and infrastructure, some activities were done such as planning the required facilities and procuring as well as maintaining facilities and infrastructure through BOS funds.